Probiotication of Plum Pulp and Conditions Effects Freeze-Drying in Cell Viability, Functional Properties and Antioxidant Activity - Mailson Gregório; Morgana Araújo; Aline Albuquerque; Thais Rodrigues; Newton C. Santos; Maria Tereza Fonseca; Maria Eduarda da Costa; Anna Tomé; Josivanda Gomes; Deyzi Gouveia; Hugo M. Lisboa; Ana Paula Rocha (Foods)
This study investigated the effects of fermenting plum pulp with Bifidobacterium animalis ssp. lactis (BAL) on its physicochemical and bioactive properties, as well as the optimization of the freeze-drying (FD) process to develop a fruit-based probiotic delivery system. Fermentation significantly reduced the pH and total acidity of the pulp, achieving a cell viability of 11 log CFU/mL. The FD process was optimized using a factorial design, with maltodextrin concentration (3, 5, and 7%) and freezing temperature (−150, −100, and −50 °C) as variables. The P2 experiment, which used 7% maltodextrin and freezing at −150 °C, showed the best results in terms of yield (25.67%), cell viability (8 log CFU/g), and probiotic survival rate (97.66%). Samples P5, P6, and P7, prepared with 5% maltodextrin and freezing at −100 °C, exhibited the highest levels of bioactive compounds and antioxidant activity (p < 0.05). During 28 days of storage, all samples maintained cell viability without significant logarithmic reduction. In summary, probiotic plum powders offer an excellent plant-based alternative for probiotic consumption, providing safe levels of beneficial bacteria and bioactive compounds with antioxidant action, meeting health and nutrition needs.